EVALUASI PENYIMPANAN DAN DISTRIBUSI OBAT DI DINAS KESEHATAN KABUPATEN REJANG LEBONG - , Sofan Wahyudi; , Prof. Dr. Dra. Sri Suryawati, Apt. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background : In medicine management, storage and distribution function are of importence to ensure the quality of medicine that will be used in health service. Good medicine distribution should include quality assurance system so that the efficacy/quality, safety and legitimacy of the medicine are guaranteed when they reach the patient. Pharmaceutical and Medical Devices Section of Rejang Lebong Health office is a section under the Health Service and Pharmaceutical Department. This Department was established following the regulation No. 38 of 2008, was the function to manage medicine and medical supplies, including the storage and distribution of medicines to health centers. Some problems related to drugs storage and distributions in the Health Office in Rejang Lebong District are the damaged and expired medicine the discrepancy between the the record and physical counting, storage that does not comply with the standard procedure and stock outs. Therefore, there was a need to evaluate the storage and distribution of medicine in Rejang Lebong District Health Office. Method: This study applied observational descriptive analytic case study design. Descriptively because the research was conducted to capture a condition or a phenomenon that occurs in a particular subject group. Data taken conducted retrospectively. Qualitative data collection was conducted by in-depth interviews and observation were documents of storage and distribution. Result : It was found that, the score of medication storage practices was 83.35 %, the average percentage variation in the physical inventory to the inventory stock cards was 0.0046%, the average percentage of stockout was 25.51%, percentage item of indicator drug in stock was 72.72%, the number of items of expired drugs of total drug items was 21.87%, percentage of the value of expired drugs was 0.28%, percentage of defective medicine value to the value of drug spending of the year was 0, 0053%, no damage of refrigerator was reported, the level of attendance officer in one year was 85.95%, and the score of drug distribution practices was 91.6%. Conclusion: The storage and distribution practice of medicine in the Rejang Lebong District Health Office in did not conform with the requirerements.